Harnessing Natural Killer Cell Innate and Adaptive Traits in HIV Infection - Alrubayyi, Aljawharah; Ogbe, Ane; Moreno Cubero, Elia; Peppa, Dimitra (Frontiers in Cellular and Infection Microbiology, 2020)
Despite efficient virological suppression on antiretroviral therapy (ART), people living with HIV (PLWH), experience an increased burden of premature co-morbidities, such as cancer and end-organ disease. With remaining challenges in terms of access to therapy, adherence and potential long-term drug toxicity, improving their long-term healthcare outcome, including new strategies for HIV clearance, remains a global priority. There is, therefore, an ongoing need to better characterize and harness the immune response in order to develop new strategies and supplement current therapeutic approaches for a “functional” cure. Current efforts toward HIV eradication to enhance immune recognition and elimination of persistently infected cells have highlighted the need for an optimized “kill” approach. Natural killer (NK) cells play an important role in antiviral defense and by virtue of their innate and adaptive features hold great promise as a focus of “kill” efforts. Galvanized by advances in the cancer field, NK cell exploitation, represents a transformative approach to augment HIV therapeutic modalities, circumventing many of the limitations inherent to T cell approaches. In this review we will discuss recent advances in our understanding of the development of NK cell adaptive/memory responses in HIV infection and highlight new and exciting opportunities to exploit the beneficial attributes of NK cells for HIV immunotherapy.